Structural analysis and immunoregulation activity comparison of five polysaccharides from Angelica sinensis. (20th April 2016) - Wang, Junmin; Ge, Beilei; Li, Zihong; Guan, Fangxia; Li, Feifei
Highlights: Four fractional and total Angelica sinensis polysaccharides were obtained. The structural characters, Mw and monosaccharide compositions were analyzed. Immunomodulatory activities in vitro were determined. The relationship between the structures and bioactivities was evaluated. Abstract: Four fractional polysaccharides (CAPS30, CAPS50, CAPS70 and CAPS80 ) and total polysaccharides (CAPSt ) were obtained from Angelica sinensis . Their structures were identified by Fourier transform-infrared spectroscopy (FT-IR), molecular weights were evaluated by high performance gel permeation chromatography (HPGPC) and compositions were analyzed by gas chromatography–mass spectrometry (GC–MS). Their immunoregulation activities were further compared in vitro. The results showed that they displayed different structural features and immuno-enhancement activities. They all could cause the proliferation of the lymphocyte, up-regulate stimulate the productions of IFN-γ, IL-2, IL-6 and TNF-α secretion in the peripheral lymphocytes. Further experiments showed that CAPS50 and CAPS70 could increase the ratio of CD3 + CD56 + cells to some extent. These indicated that five CAPSs displayed different activities which were associated with their different structural characteristics and CAPS70, with the molecular weights of 20.82 kDa and consisting of mannose and glucose in the molar ratio of 1.20:1.01, possessed the strongest immuno-enhancement activity.